Lateral Boundary of Cirrus Cloud from CALIPSO Observations. Issue 1 (December 2017) - Fu, Yunfei; Chen, Yilun; Li, Rui; Qin, Fang; Xian, Tao; Yu, Lu; Zhang, Aoqi; Liu, Guosheng; Zhang, Xiangdong
Absract Due to the thinness and small scale of cirrus clouds, its lateral boundary may be missed by conventional passive remote-sensing techniques and climate models. Here, using satellite observations in June–August from 2006 to 2011, a global dataset for the cirrus cloud lateral boundary (CCLB) was established. The results indicate that the optical properties, such as the lidar backscatter, the depolarization ratio and the optical depth, sharply decrease from cloudy regions to clear-sky regions. There are significant regional differences in optical properties and height and thickness of the CCLB. Based on a quantitative estimation, the strongest longwave warming effects (>0.3 W m−2 ) are found near the Equator and over tropical continents. The global average longwave warming effect of the CCLB is at least 0.07 W m−2, which is much larger than some of the radiative forcings considered in the Intergovernmental Panel on Climate Change (IPCC) reports. Specifically, the CCLB in traditional "clear-sky" region may be totally missed by current models and IPCC reports, which contributes 28.25% (~0.02 W m−2 ) of the whole CCLB radiative effect, twice greater than contrail effect. It is recommended that the CCLB effect should be taken account in future climate models and the next IPCC reports.